2021
DOI: 10.3390/healthcare9040424
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Mental Health: A Study of Stress, Resilience, and Depression among the Older Population in Pakistan

Abstract: Extending studies of the adverse effects of SARS-2 coronavirus on general health consequences, this research explores complexities related to the mental health of the elderly as a result of pandemic-related stress. The study addresses this issue by using resilience theory to examine the effects of fear and exposure related to COVID-19 and depression. Besides, our study examines the moderating effects of self-efficacy in order to provide an understanding of how the coping abilities of the elderly may mitigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 56 publications
1
25
0
3
Order By: Relevance
“…This result can be interpreted that the fear of COVID-19 affects the general self-efficacy of people negatively; that is, as the fear of COVID-19 increases, the self-efficacy of individuals decreases. The results of the current study are consistent with the results of the previous studies, which found a negative association between fear of COVID-19 and general self-efficacy (Mumtaz et al, 2021 ; Okan, 2021 ). Moreover, the results of this study support Bandura's ( 1995 ) view that positive mood increases perceived self-efficacy while a negative mood weakens it.…”
Section: Discussionsupporting
confidence: 93%
“…This result can be interpreted that the fear of COVID-19 affects the general self-efficacy of people negatively; that is, as the fear of COVID-19 increases, the self-efficacy of individuals decreases. The results of the current study are consistent with the results of the previous studies, which found a negative association between fear of COVID-19 and general self-efficacy (Mumtaz et al, 2021 ; Okan, 2021 ). Moreover, the results of this study support Bandura's ( 1995 ) view that positive mood increases perceived self-efficacy while a negative mood weakens it.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, having discussed the behavioural and psychological aspects, this study mainly engages conceptual work and policy analysis on the subject rather than sociological studies of structural interpretations of the rules and behaviours of quarantine. In previous studies, some researchers showed the effect of prolonged quarantine was associated with poor mental health, particularly post-traumatic stress symptoms, anger, and avoidance behaviour ( 6 , 13 , 14 ), and at the behavioural level, the regulations about the behavioural rules are discussed, such as a distance of one metre between customers in bars and coffee shops and the rules reducing interpersonal interactions in social meeting. Thus, this study constructs a four-modes frame of analysis and test explanatory power of these modes in the policy practises as the strategy of prevention in the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Social and economic variables can have a huge effect on how healthy we are and how long we survive. ese variables influence our capacity to make healthy decisions, afford medical treatment and housing, and deal with stress, among other things [25].…”
Section: Discussionmentioning
confidence: 99%